Susan I. Rotroff: Hellenistic Pottery. The Plain Wares, Agora 33 - Kögler, Patricia (Journal of Hellenistic Pottery and Material Culture, 2020)
Agora Vol. 33 is the 3rd and thus far last tome of the publications of Hellenistic pottery from the Athenian Agora. It follows the volumes on the mold- and wheel-made tablewares in volls. 22 (Moldmade Bowls) & 29 (Wheelmade Tableware) of the series. Now SR presents the ›Plain Wares‹ - in German archaeological slang inaptly and derogatorily called ›coarse utilitarian ceramics‹ – which most likely is that part of the materials recovered during the decades of American excavations that is the most difficult to work on. A common characteristic for vessels of this category is – as SR points out in her introduction – the lack of surface covering which is characteristic for Fine Ware.